2006
DOI: 10.1074/jbc.m602750200
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan Oligosaccharides Induce Matrix Metalloproteinase 13 via Transcriptional Activation of NFκB and p38 MAP Kinase in Articular Chondrocytes

Abstract: Hyaluronan exerts a variety of biological effects on cells including changes in cell migration, proliferation, and matrix metabolism. However, the signaling pathways associated with the action of hyaluronan on cells have not been clearly defined. In some cells, signaling is induced by the loss of cell-hyaluronan interactions. The goal of this study was to use hyaluronan oligosaccharides as a molecular tool to explore the effects of changes in cell-hyaluronan interactions and determine the underlying molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
114
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(121 citation statements)
references
References 70 publications
(91 reference statements)
5
114
0
2
Order By: Relevance
“…Mengshol et al have assessed the role of NF-kB in MMP-13 transcription in chondrocytes and found that, besides JNK and p38, NF-kB signaling is required for the IL1b-mediated induction of MMP-13 (Mengshol et al 2000). Although the promoter of MMP-13 does not contain consensus NF-kB binding sites (Burrage et al 2006), the link between NF-kB activation and MMP-13 induction has been further demonstrated in a previous study on the effect of hyaluronan oligosaccharides in articular chondrocytes (Ohno et al 2006). We show here that, indeed, NF-kB p65/p50 overexpression leads to MMP-13 promoter transactivation and that CSE suppresses the p65/p50-driven MMP-13 promoter activation, thereby suggesting that CSE's MMP-inhibitory actions are related to its blockade of the NF-kB signaling.…”
Section: Discussionmentioning
confidence: 87%
“…Mengshol et al have assessed the role of NF-kB in MMP-13 transcription in chondrocytes and found that, besides JNK and p38, NF-kB signaling is required for the IL1b-mediated induction of MMP-13 (Mengshol et al 2000). Although the promoter of MMP-13 does not contain consensus NF-kB binding sites (Burrage et al 2006), the link between NF-kB activation and MMP-13 induction has been further demonstrated in a previous study on the effect of hyaluronan oligosaccharides in articular chondrocytes (Ohno et al 2006). We show here that, indeed, NF-kB p65/p50 overexpression leads to MMP-13 promoter transactivation and that CSE suppresses the p65/p50-driven MMP-13 promoter activation, thereby suggesting that CSE's MMP-inhibitory actions are related to its blockade of the NF-kB signaling.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, inhibition of NF-κB p65 pathways by PDTC, TPCK and Bay 11-7082 also reversed the leptin-induced increase of MMP-13 production. MMP-13 expression is also reported to be induced via NF-κB activation in chondrocytes (Liacini et al 2003;Ohno et al 2006). Since Morash et al (2000) reported that C6 glioma cells do not express long form of leptin receptor (ObRl), all the signal transduction observed in this study is due to the activation of short form of leptin receptor (ObRt).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear factor κB (NF-κB) is one of the transcription factors which can drive MMP-13 expression (Liacini et al 2003;Ohno et al 2006). Here we further examined whether NF-κB is involved in the action of leptin.…”
Section: Involvement Of P38 Mapk and Nf-κb Signaling Pathways In Leptmentioning
confidence: 99%
“…Streptomyces hyaluronidase (H1136) was purchased from Sigma. Pharmaceutical grade high molecular mass HA (ARTZ) was a gift from Seikagaku Co. Hyaluronan oligosaccharides were generated from human rooster comb hyaluronan (Sigma), as described previously (27).Specific antibodies used for analysis were goat anti-AD-AMTS4 (sc-16533, clone K-20, lot I2010; Santa Cruz Biotechnology), rabbit anti-MMP13 (sc-30073, clone H-230, lot F1312; Santa Cruz Biotechnology), rabbit anti-TSG6 (sc-30140, clone FL-277, lot C0112; Santa Cruz Biotechnology), rabbit affinitypurified anti-CD44 cytoplasmic tail antisera (1:5,000) (46), and ␤-actin (A1978, clone AC-15, lot 065M4837V; Sigma). The following antibodies were all obtained from Cell Signaling Technology: mouse anti-Myc (catalog no.…”
mentioning
confidence: 99%